(untitled) (Canadian Hematology Today, 2022)
Myelodysplastic neoplasms (MDS) are a group of clonal hematopoietic stem cell disorders characterized by ineffective hematopoiesis, cytopenia, and morphologic dysplasia. Most cases of MDS are de novo, and a minority are post cytotoxic therapy About 30% of the cases will eventually progress to acute myeloid leukemia (AML), with a higher incidence among the higher-risk MDS group. MDS is a rare disorder with an overall incidence of 3.7-4.8/100,000; the rate increases with age.